Stiffness and strength of laminated composite when exposed to ordinary saltwater condition [electronic resource] - 411241 Faizul Ikram Mohd. Noor (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007